2021
DOI: 10.4239/wjd.v12.i9.1539
|View full text |Cite
|
Sign up to set email alerts
|

Role of an acidic environment in the treatment of diabetic foot infections: A review

Abstract: Management of diabetic foot ulcers is the biggest challenge to the clinician, as conventional antibiotic therapies and local wound care have their own limitations. They are not effective for control of infections and promotion of healing because of cytotoxic effects. In view of cytotoxicity of routinely used topical antiseptic agents, this article focuses on the search of an ideal topical antiseptic agent that is safe and effective in controlling infectious agents and also in promoting the healing process. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…)[ 3 , 16 - 20 ]. The adverse effects of topical antimicrobials are concerning[ 21 ]. The exact duration of antibiotics for different severities of DFU infections is unknown[ 8 , 22 ].…”
Section: Challenges During Management Of Dfumentioning
confidence: 99%
See 2 more Smart Citations
“…)[ 3 , 16 - 20 ]. The adverse effects of topical antimicrobials are concerning[ 21 ]. The exact duration of antibiotics for different severities of DFU infections is unknown[ 8 , 22 ].…”
Section: Challenges During Management Of Dfumentioning
confidence: 99%
“…Conventionally available and naturally occurring acids are also used for the topical management of chronic and infected wounds like DFU. The acidic milieu favours wound healing by antimicrobial action as well as promoting inflammatory and proliferative phases[ 21 ].…”
Section: Acids In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiseptics are a class of drugs that can prevent the growth or damage of microorganisms in living tissues or on the surface of living tissues. Halogenated compounds, alcohol-based agents, and biguanides are often used as antiseptics primarily for chronic wound care because they effectively inhibit bacterial reproduction and promote resistance to the external environment [ 51 , 52 ]. (4) Alginate dressing: Alginate dressing consists of alginate salts, which are highly absorbent and hemostatic and suitable for highly exuding wounds.…”
Section: Diabetic Wounds and Diabetic Dressingsmentioning
confidence: 99%
“…Diabetic foot ulcers are one of the most challenging complications of diabetes[ 2 - 4 ]. Previous study found that a group of traditional Chinese medicine (TCM) ( e.g.…”
Section: To the Editormentioning
confidence: 99%